Shelter Use Influences Red Fox Spatial Ecology in the Central Australian Desert During a Period of Low Rainfall - Young, Lauren I.; Skinner, Kirsten; Tyne, John; Edwards, Glenn (Austral ecology, 2025)
ABSTRACT The establishment of red foxes across much of continental Australia has contributed to the decline and extinction of many native species. Managing this invasive species effectively requires understanding variability in the species' ecology across the different environments it inhabits. We present GPS collaring data from two red foxes in different desert environments during a period of low rainfall in central Australia. Both foxes were range resident and occupied home ranges comparable in size to the largest previously published home ranges for the species. Core ranges were centred on frequently used sites, including daytime resting sites for both fox individuals and nighttime activity sites for one. The two foxes had distinct nightly range use patterns, which appeared to be influenced by the location of regularly used daytime resting sites. One fox regularly crossed its home range in a night, moving between high‐use sites, while the other primarily used one daytime resting site, traversing different parts of its broader range each night. This information enhances the limited knowledge of red fox spatial ecology in desert environments and provides insights to inform targeted management programmes in these regions.